Changes in Gene Expression Patterns in the Tumor Microenvironment of Head and Neck Squamous Cell Carcinoma Under Chemoradiotherapy Depend on Response - Doescher, Johannes; von Witzleben, Adrian; Boukas, Konstantinos; Weissinger, Stephanie E.; Thomas, Gareth J.; Laban, Simon; Thomas, Jaya; Hoffmann, Thomas K.; Ottensmeier, Christian H. (Frontiers in Oncology, 2022)
Chemoradiotherapy (CRT) is a standard treatment for advanced head and neck squamous cell carcinoma (HNSCC). Unfortunately, not all patients respond to this therapy and require further treatment, either salvage surgery or palliative therapy. The addition of immunotherapy to CRT is currently being investigated and early results describe a mixed response. Therefore, it is important to understand the impact of CRT on the tumor microenvironment (TME) to be able to interpret the results of the clinical trials. Paired biopsies from 30 HNSCC patients were collected before and three months after completion of primary CRT and interrogated for the expression of 1392 immune- and cancer-related genes. There was a relevant difference in the number of differentially expressed genes between the total cohort and patients with residual disease. Genes involved in T cell activation showed significantly reduced expression in these tumors after therapy. Furthermore, gene enrichment for several T cell subsets confirmed this observation. The analysis of tissue resident memory T cells (TRM) did not show a clear association with impaired response to therapy. CRT seems to lead to a loss of T cells in patients with incomplete response that needs to be reversed. It is not clear whether the addition of anti-PD-1 antibodies alone to CRT can prevent treatment failure, as no upregulation of the targets was measurable in the TME.